Optimization of Fermentation and Freeze-Drying Processes to Enhance the Productivity and Stability of a Probiotic, Lactobacillus Salivarius I 24 - Lim, Chin Ming (2006)
Production of Lactobacillus salivarius I 24, a probiotic strain for chicken; was studied in batch and fed-batch fermentations using shake flasks and a 2-L stirred tank fermenter. In addition, preservation of L. salivarius I 24 using freeze-drying technique was also carried out. From a preliminary study, glucose and yeast extract were found to be the best carbon and nitrogen sources, respectively. Response surface method (RSM) was then used to optimize the culture medium for the growth of L. salivarius I 24. The factors investigated were yeast extract, glucose and initial culture pH. A polynomial regression model with cubic and quartic terms was used for the analysis of the experimental data. Estimated optimal conditions of the factors for the growth of L. salivarius I 24 were: 3.32% (w/v) of glucose, 4.31% (w/v) of yeast extract and an initial pH of 6.10. Further improvement of cell production was made by using an optimization approach in the process condition. Aeration, pH, mixing and inoculum size were investigated. Cell production and viability were greatly influenced by the culture pH compared to other parameters. The optimum culture conditions for the cultivation of L. salivarius I 24 in the 2-L stirred tank fermenter were as follows: impeller tip speed, 0.42 m/s; pH, 6.10, and inoculum size of 10% (v/v) in facultative condition. Under these conditions, the final cell viability was 14.1 x 109 cfu/mL; viable cell yield was 4.37 x 1011 cfu/gGlucose and productivity was 17.59 x 108 cfu/mL.h. A model employing the logistic and Leudeking-Piret equation for mixed-growth associated product formation was found to be sufficient to describe growth of L. salivarius I 24 and lactic acid production. The general kinetic parameters were calculated from the analysis of a large number of experimental data from batch fermentations. The calculate value of μmax was 0.69 h-1. Fed-batch cultivation was used in an attempt to further improve biomass production of L. salivarius I 24 by enhancing carbon flux to cell built up and reduce the flux to lactic acid production. Stepwise fed-batch cultivation (SFBC) gave better result than constant fed-batch cultivation (CFBC) when operated at a μ of 0.3 h-1, which gave 528% improvement in viable cell counts when compared to CFBC. Results obtained form SFBC at a μ of 0.3 h-1 indicated that this cultivation mode might be a good alternative for L. salivarius I 24 production as higher cell concentration and lower lactic acid production could be achieved compared to batch cultivation. Prior to the freeze-drying process, addition of protective agents could effectively improve the viability of the freeze-dried L. salivarius I 24 cultures. Among the protective agents investigated, 9.85% (w/v) of skim milk and 10.65% (w/v) of sucrose demonstrated the best survival rate of L. salivarius I 24. Better survival of L. salivarius I 24 during freeze-drying was also observed when the pH and temperature were controlled during cultivation, and when the cultures were frozen at –80oC for 5 h before the freeze-drying process. Under these conditions, the highest survival rate, which was 65.2%, was achieved, and the viable counts of L. salivarius I 24 remained almost stable after 6 months of storage at –30oC.